Water‐soluble protein molecular weight distribution and effects on wheat malt quality during malting. Issue 4 (30th September 2014) - Xie, Lan; Jin, Yuhong; Du, Jinhua; Zhang, Kaili
<x xml:space="preserve">Abstract</x> The content and the molecular weight distribution of wheat water‐soluble proteins during malting were determined. Also, the relationships between wheat malt characteristics and water‐soluble protein molecular weight distributions were studied. The water‐soluble protein content was found to increase during malting and the increment was most significant on the first and second days. The molecular weight distribution of the wheat water‐soluble protein was analysed by high‐pressure size exclusion chromatography (HPSEC) and sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS‐PAGE) methods. The HPSEC method showed that the content of all six molecular weight fractions (>24.4, 9.8–24.4, 3.9–9.8, 2.5–3.9, 0.4–2.5 and <0.4 kDa) of the water‐soluble protein increased. Among these, there was a considerable increase in the 0.4–2.5 and 2.5–3.9 kDa fractions. The >24.4, 9.8–24.4 and 3.9–9.8 kDa fractions showed a declining trend during steeping but an increase during the first 2 days of germination. The content of the 9.8–24.4 kDa fraction increased during the process of kilning. Wheat had a high percentage of the >24.4 and 9.8–24.4 kDa fractions, while wheat malt had a high percentage of the 2.5–3.9 and 0.4–2.5 kDa fractions. The molecular weight fractions of the water‐soluble protein had negative correlations with wheat malt viscosity and positive correlations with wheat malt extract. The SDS‐PAGE analysis showed that the band of the 60 kDa water‐soluble protein faded, while the bands of the 56, 44 and 12–15 kDa water‐soluble proteins became darker during malting. Copyright © 2014 The Institute of Brewing & Distilling